Phenomenology of Sexual Dysfunctions in Chemical Warfare Victims of Sardasht City - B. Melkari; K. Farahbakhsh; N. Farrokhi; A. Motamedi (Afarand Scholarly Publishing Institute, 2020)
Aims: Sexual dysfunction is one of the most important factors that can play a fundamental role in the individual and social health and adjustment of people. Chemical injury is one of the cases that can be considered as a serious factor in the occurrence or aggravation of sexual dysfunction by causing organic and psychological changes in male and female victims. The purpose of this study was to identify sexual dysfunctions in chemical warfare victims in Sardasht city. Participants & Methods: This qualitative phenomenological research was carried out in 2018 using grounded theory method among all chemical warfare victims in Sardasht city. At first, Hurlbert Index of Sexual Desire (HISD) was distributed among the identified individuals and 60 chemical victims (30 females and 30 males) with low score were selected by purposive sampling method for participation in the study. Semi-structured interviews were used to collect data. All interviews were recorded and then transcribed, and finally the data were analyzed using the Colaizzi's seven step process and grounded theory method. Findings: The core code for "multiple sexual disfunctions" included 9 selected codes. Selected codes were identified with their primary and secondary concepts. Conclusion: Identified sexual disfunctions include disorder in initiating sexual relations, lack of sexual arousal, lack of perception of sexual pleasure, sexual organ dysfunction, lack of sexual desire, impotency, erectile dysfunction, multi-faceted disorder in ejaculation and masturbation.